Review Article: Analysis of The Food Additive Rhodamine B in Foods Circulated in The Public - Kanata, Nur Ramdhani; Putri , Chairatun Hisyani; Agustiani, Eti; Nurain, Siti; Syaharani, Ninda; Sutanti, B. Novia Rahmadita; Putri, Ni Luh Eka Sudiawati; Maulidya, Selvir Anandia Intan (Jurnal Biologi Tropis, 2026)
Food safety is very important, especially when it comes to snacks that kids and adults eat a lot of. Rhodamine B is still often used as a food coloring, even though it has been banned because it can cause serious health problems, like liver damage and a higher risk of cancer from long-term exposure. This review seeks to investigate the occurrence of Rhodamine B in diverse food products available in the community and to evaluate the analytical methodologies employed in prior research. The research methodology employed is a literature review of national articles published between 2020 untill 2025, utilizing a literature search via Google Scholar with keywords pertinent to Rhodamine B and food analysis. Data were analyzed descriptively according to sample type and analytical methods, including color reaction tests, wool thread tests, thin layer chromatography (TLC), and UV-Vis spectrophotometry, along with the outcomes of Rhodamine B identification. The findings indicated that Rhodamine B was still present in various food items, particularly traditional red cakes, school snack crackers, unbranded jam, red velvet cakes, and certain steamed cakes. Layer cakes, jelly-based foods, cilok sauce, and shrimp paste, on the other hand, were said to not have Rhodamine B in them. This finding stresses the need for ongoing food monitoring and the use of good analytical methods.